PENGARUH LINGKUNGAN SEKOLAH ISLAMI DAN TEMAN SEBAYA TERHADAP SIKAP TOLERANSI ANTARUMAT BERAGAMA SISWA KELAS X SMA MUHAMMADIYAH 4 DEPOK - Muhammad Alif Dwiki; Annisa Nurul; Saripudin; Muhammad Alfi Syahrin (LP2M IAI Darussalam Martapura, 2026)
This study was motivated by the importance of strengthening students’ interreligious tolerance attitudes in educational settings as an effort to maintain social harmony in a multicultural society. Schools play a strategic role in character development through a conducive educational environment and positive social interactions. This study aimed to examine the influence of the Islamic School Environment and Peer Groups on the Interreligious Tolerance Attitudes of tenth-grade students at SMA Muhammadiyah 4 Depok. The study employed a quantitative approach using a correlational survey method. The population consisted of 90 students, with 58 valid respondents selected through questionnaire-based data collection using a five-point Likert scale. Data were analyzed using multiple linear regression with IBM SPSS Statistics. The analytical procedures included descriptive statistics, normality testing, multicollinearity testing, t-tests, F-tests, and coefficient of determination analysis. The findings revealed that the Islamic School Environment had a positive and significant effect on students’ interreligious tolerance attitudes (β = 0.347; p = 0.021). Meanwhile, Peer Groups showed a positive but statistically insignificant effect (β = 0.219; p = 0.085). Simultaneously, the Islamic School Environment and Peer Groups significantly influenced students’ interreligious tolerance attitudes (F = 10.920; p = 0.000), with a contribution of 28.4% (R² = 0.284). This study concludes that the Islamic School Environment is the most dominant factor in shaping students’ interreligious tolerance attitudes. The study contributes empirical evidence that a moderate, inclusive, and rahmatan lil ‘alamin-oriented Islamic school culture can serve as an effective strategy for fostering tolerance and strengthening character education among secondary school students.